Flexural Performance of a Semi-Precast Two-Way Slab with AAC Infill and Hybrid Bamboo–Steel Reinforcement under Point Loading - Dwi Putra, Bagus Ginanjar; Dewi, Sri Murni; Wisnumurti (Rekayasa Sipil, 2025)
This study investigates the flexural performance of a semi-precast two-way ribbed slab system composed of a ferrocement bottom layer, Autoclaved Aerated Concrete (AAC) infill, and a hybrid bamboo–steel reinforcement configuration, subjected to a centrally applied point load. Two specimens were tested experimentally to evaluate their deflection behavior, crack patterns, and ultimate load capacity. The Finite Element Method (FEM) was also used to simulate the slab’s response and validate the experimental outcomes. The experimental results indicated ultimate load capacities of 5277 kg and 5000 kg for specimens S1 and S2, with corresponding maximum deflections of 6.80 mm and 6.90 mm. Diagonal cracks were observed originating from the load application point, which was consistent with flexural behavior under concentrated loading. The FEM simulation predicted an ultimate load of 5500 kg and a maximum deflection of 6.38 mm, resulting in a load deviation of +4.44% and a deflection deviation of –6.97% relative to the experimental average. Despite idealized assumptions in the numerical model, the FEM results showed good agreement with experimental observations in terms of deformation patterns and stress distribution. These findings demonstrate the potential of the proposed slab system for structural applications incorporating lightweight materials and alternative reinforcements. Further studies are recommended to explore its dynamic performance and practical feasibility in sustainable construction practices.